Left ventricular outflow tract obstruction due to anomalous mitral valve: successful mitral valve replacement in a four month old infant. Issue 4 (October 1986) - Morais, P; Westaby, S; Hallidie-Smith, K A
Abstract : A four month old infant was investigated for heart failure was found to have mitral incompetence and severe subvalvar aortic stenosis. The left ventricular outflow tract obstruction was found to be due to an anatomically anomalous mitral valve. The obstruction could only be relieved by removal of the mitral valve and its replacement with a St Jude's prosthesis. Two years after operation the child is fit and active. There have been no difficulties with anticoagulant treatment.